Association between the Body Roundness Index and osteoarthritis: A population-based study. - Yue Qiu; Huangyi Yin; Jinzhi Meng; Yang Cai; Jun Yao (PLoS ONE)
Background Obesity is recognized as an independent risk factor for the development of osteoarthritis (OA). The Body Roundness Index (BRI) represents a novel metric for assessing obesity, yet its connection to OA remains unclear. This research aims to explore the potential association between BRI and OA. Methods We analyzed data from 20,564 participants who were part of the National Health and Nutrition Examination Survey (NHANES) conducted between 2007 and 2016. The association between BRI and the prevalence of OA was examined using multifactorial logistic regression and restricted cubic spline (RCS) analysis. To ensure the reliability of the findings, we conducted a stratified analysis. Results The average BRI among the participants was 5.18 (0.03), with an OA prevalence of 11.98%. Following adjustment for all covariates, continuous BRI exhibited a significant positive association with OA (OR: 1.19, 95% CI: 1.15-1.24, P < 0.0001). Participants in the top quartile of BRI showed a 153% higher prevalence of OA relative to individuals in the lowest quartile (OR: 2.53, 95% CI: 2.01-3.19, P < 0.0001). The RCS curve demonstrated a linear relationship between BRI and OA. Subgroup analysis examined that the observed relationship was significant exclusively among individuals with a BMI ≥ 30 kg/m². This association remained unaffected by variables such as race, age, gender, hypertension, cardiovascular disease (CVD), or diabetes. Conclusion An increased BRI is associated with a higher prevalence of OA, particularly in obese populations. BRI is expected to become a valuable indicator for identifying individuals at high risk of OA.